(untitled) (Revista de Educação Continuada em Medicina Veterinária e Zootecnia do CRMV-SP, 2013)
Because of the high costs of rabies intramuscular (IM) post exposure prophylaxis (PEP) protocols, cheaper intradermal (ID) protocols using reduced doses were developed in some countries and validated by WHO. Due to lack of data on the efficacy of a protocol using ID and IM route successively, WHO recommends using only one route of administration per protocol. In France and many other high resource countries, no packaging adapted to ID route is available and only IM regimens are authorized by the marketing authorization, leading doctors not to follow WHO recommendations for patients having started an ID protocol abroad. As there is no study available on ID-IM switch efficacy, we sought to evaluate it with two objectives: to describe serological efficacy of our daily practice and to assess if there is a need to alert our national health authorities about the need of authorizing the ID route.